Pro Crystal Enterprise/Business Objects XI Programming72 - Ganz, Carl (Apress, 2012)
BusinessObjects XI is a powerful middleware server product that allows you to distribute your Crystal Reports and BusinessObjects reports to the enterprise. Out of the box it offers an intuitive, feature-rich front end that allows system administrators to load reports to the repository as well as schedule them to run, track report histories, send notifications, monitor events, and many other features as well. It also offers a powerful object model that allows you to create custom solutions for your enterprise applications. It is this object model that is the topic of this book.